Pemodelan Sistem Antrian Pelayanan BPJS (Badan Penyelenggara Jaminan Sosial) Menggunakan Petri Net dan Aljabar Max-Plus - Simbolon, Yohana L.; Rumlawang, Francis Y.; Dahoklory, Novita; Patty, Henry W. M.; Taihuttu, Pranaya D. M.; Wattimena, Abraham Z. Wattimena (Tensor: Pure and Applied Mathematics Journal, 2025)
Hospitals are one of the health facilities that serve patients with various types of services, including BPJS patients. Like other hospitals, the queue system is a challenge in service management, especially in outpatient services. The imbalance between the number of patients coming and the service capacity can cause long waiting times. In this study, outpatient queue modeling was carried out at Leimena General Hospital, Ambon, using Petri Net to describe the service flow, and Max-Plus algebraic analysis was applied to estimate patient waiting times more accurately. The simulation results showed that increasing the number of resources, such as adding registration counters and doctors in the laboratory, was able to significantly reduce patient waiting times at various stages of service, especially in the pharmacy. This modeling shows that the Petri Net and Max-Plus approaches are not only effective in mapping the queue system, but can also be used as a basis for decision making in optimizing hospital services. This study is expected to be a reference for hospitals in improving service efficiency and for further researchers to develop more complex models by considering additional relevant variables.